Inflammatory Bowel Diseases: Epidemiological Features and Treatment - Kurekci, Derya Deniz; Bektas, Ahmet; Ayyildiz, Talat; Goren, Ibrahim; Yildirim, Beytullah (Wiley, 2018)
…
Keywords: Ulcerative Colitis; Crohn's Disease; Epidemiology